Peran Mahasiswa Magang dalam Mendukung Administrasi dan Pengelolaan Piutang Pelanggan pada PDAM Kabupaten Lombok Timur - Naura Bafadal; Ribi; Ruhul Maydi Adnin; Anggraini Palinda; Sulhan Hadi (BALE LITERASI, 2026)
Internship programs are a form of experiential learning designed to bridge the gap between theoretical knowledge acquired in academic settings and practical experience in the workplace. This study aims to describe the implementation of internship activities and analyze the role of students in supporting administrative and operational activities at the Regional Water Supply Company (PDAM) of East Lombok Regency. The method used in this study is a descriptive approach, utilizing observation, direct practice, and documentation techniques during the internship period. The results show that students actively contributed to administrative activities, including data entry of customer information, billing records, and monitoring customer receivables through the existing system. In addition, students were involved in field activities such as direct billing to customers, which enhanced their communication and interpersonal skills. The use of digital administrative systems also provided valuable insights into the importance of accuracy and data management. The internship experience significantly improved both technical and soft skills of students, such as administrative competence, communication ability, and work discipline. Therefore, internship programs are proven to enhance students’ work readiness while also contributing to the operational performance of the institution.